Proceedings of the 23rd ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2017
DOI: 10.1145/3097983.3098047
|View full text |Cite
|
Sign up to set email alerts
|

Learning Certifiably Optimal Rule Lists

Abstract: We present the design and implementation of a custom discrete optimization technique for building rule lists over a categorical feature space. Our algorithm produces rule lists with optimal training performance, according to the regularized empirical risk, with a certificate of optimality. By leveraging algorithmic bounds, efficient data structures, and computational reuse, we achieve several orders of magnitude speedup in time and a massive reduction of memory consumption. We demonstrate that our approach pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
220
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(238 citation statements)
references
References 43 publications
(51 reference statements)
3
220
0
1
Order By: Relevance
“…In the criminal justice context, Jung et al (2017) show that "simple rules that consider only two features -age and prior FTAs [failureto-appear in court] -perform nearly identically to state-of-the-art machine learning models (random forest and lasso regression) that incorporate all 64 available features". 6 Other authors have shown that it is possible to construct simple two-feature prediction tools that perform as well as the well-known risk assessment tool COMPAS, which has access to 136 input variables, or a non-linear support vector machine trained on 7 input variables (Angelino et al, 2017;Dressel and Farid, 2018).…”
Section: Algorithmic Risk Assessment In Criminal Justicementioning
confidence: 99%
“…In the criminal justice context, Jung et al (2017) show that "simple rules that consider only two features -age and prior FTAs [failureto-appear in court] -perform nearly identically to state-of-the-art machine learning models (random forest and lasso regression) that incorporate all 64 available features". 6 Other authors have shown that it is possible to construct simple two-feature prediction tools that perform as well as the well-known risk assessment tool COMPAS, which has access to 136 input variables, or a non-linear support vector machine trained on 7 input variables (Angelino et al, 2017;Dressel and Farid, 2018).…”
Section: Algorithmic Risk Assessment In Criminal Justicementioning
confidence: 99%
“…For a company like Northpointe to invest the time and effort into creating such a model, it seems reasonable to afford the company intellectual property protections. However, as we discussed, machine learning methods -either standard black-box or, better yet, recently-developed interpretable ones -can predict equally well or better than bespoke models like COMPAS (21)(22)(23)(24). For important applications like criminal justice, academics have always been willing to devote their time and energy.…”
Section: Introductionmentioning
confidence: 99%
“…Work in machine learning has shown that complicated, black-box, proprietary models are not necessary for recidivism risk assessment. Researchers have shown (on several datasets, including the data from Broward County) that interpretable models are just as accurate as black box machine learning models for predicting recidivism (21)(22)(23)(24)(25)(26). These simple models involve age and counts of past crimes, and indicate that younger people, and those with longer criminal histories, are more likely to reoffend.…”
Section: Introductionmentioning
confidence: 99%
“…A recent approach also using MDL and probabilistic rule lists (MRL) [4] is aimed at describing rather than classifying and cannot deal with multiclass problems or a large number of candidates. Interpretable decision sets (IDS) [25] and certifiable optimal rules (CORELS) [3] use similar rules but do not provide probabilistic models or predictions.…”
Section: Related Workmentioning
confidence: 99%